Perang Bubat Sebagai Inspirasi Karya Seni Lukis Dengan Teknik Chiaroscuro - Faishal Arkan; Amboro, Joko Lulut (Amerta Media, 2024)
This research is highlights the Bubat War, a controversial historical event that influenced the relationship between the Javanese and Sundanese communities. Occurring in 1357 AD, the Bubat War's authenticity is still debated, and it has left a significant impact that persists to this day. The event began with the planned marriage between Hayam Wuruk of the Majapahit Kingdom and Dyah Pitaloka of the Sunda Kingdom, but it ended in a battle with long-term social and cultural repercussions. The research questions in this study include: what are the storyline and context of the Bubat War, what underlies the selection of this event as an inspiration for creating a painting, and how is the visualization process of a painting that interprets the Bubat War using the chiaroscuro technique. The chiaroscuro technique was chosen for its ability to highlight the contrast between light and dark to convey the emotion and drama of this historical event. The creation process includes idea collection, sketching, and the application of the chiaroscuro technique to create a dramatic effect that suits the theme. This painting aims to preserve Indonesian culture and history through an artistic approach inspired by European art styles and to contribute positively to society's understanding and appreciation of the nation's historical heritage. Keywords:Bubad War, Chiaroscuro, Painting Penelitian ini mengangkat Perang Bubat, sebuah peristiwa sejarah kontroversial yang mempengaruhi hubungan antara masyarakat Jawa dan Sunda. Terjadi pada tahun 1357 M, Perang Bubat masih diperdebatkan kebenarannya dan meninggalkan dampak signifikan hingga kini. Peristiwa ini bermula dari rencana pernikahan antaraHayam Wuruk dari Majapahit dan Dyah Pitaloka dari Sunda, namun berakhir dengan pertempuran yang berdampak sosial dan budaya jangka panjang. Rumusan masalah dalam penelitian ini meliputi: bagaimana alur dan konteks cerita Perang Bubat, apa yang mendasari pemilihan peristiwa ini sebagai inspirasi dalam penciptaan seni lukis, dan bagaimana proses visualisasi karya seni lukis yang menginterpretasikan Perang Bubat menggunakan teknik chiaroscuro. Teknik chiaroscuro dipilih karena kemampuannya menonjolkan kontras antara terang dan gelap untuk menyampaikan emosi dan drama dari peristiwa sejarah ini. Proses penciptaan meliputi pengumpulan ide, pembuatan sketsa, dan penerapan teknik chiaroscuro untuk menciptakan efek dramatis yang sesuai dengan tema. Karya seni lukis ini bertujuan untuk melestarikan budaya dan sejarah Indonesia melalui pendekatan artistik yang terinspirasi oleh gaya seni Eropa, serta memberikan kontribusi positif kepada masyarakat dalam memahami dan menghargai warisan sejarah bangsa. Kata kunci: Perang Bubad, Chiaroscuro, Melukis